Effect of nanocrystalline cellulose addition on needleless alternating current electrospinning and properties of nanofibrous polyacrylonitrile meshes. Issue 5 (22nd September 2017) - Paulett, Katherine; Brayer, W. Anthony; Hatch, Katrina; Kalous, Tomáš; Sewell, Jerry; Liavitskaya, Tatsiana; Vyazovkin, Sergey; Liu, Fei; Lukáš, David; Stanishevsky, Andrei
ABSTRACT: Needleless alternating current (AC)‐electrospinning is capable of achieving high nanofiber generation rates while adding more flexibility to the process development when compared to common direct current (DC)‐electrospinning. However, AC‐electrospinning process may produce very different results than DC‐electrospinning when using the same precursors. This study demonstrated that stable AC‐electrospinning of uniform and mechanically strong polyacrylonitrile (PAN) nanofibrous meshes can be achieved at 30 ± 5 kV rms voltage when 0.75–6.0 wt % of nanocrystalline cellulose‐II with respect to PAN is added to a typical PAN precursor solution. Efficient generation (up to 2 g/h rate or 0.7 g h −1 cm −2 mass flux) of nanofibers with 250–500 nm fiber diameters has been observed when using flat fiber‐generating electrodes with diameters up to 25 mm. Depending on the amount of nanocellulose, nanofibrous nanocellulose/PAN meshes revealed large variations in tensile modulus (90–273 MPa) and yield strength (1.0–2.5 MPa), whereas the fiber diameter, air permeability, air resistance, mesh porosity, and water absorption were less affected. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45772. Abstract :